From osteoblast to osteoclast: new insights of Yin-Yang theory in bone remodeling - Dong-Feng Zhao; Cheng-Long Wang; Yong-Jian Zhao; Zhi-Lie Yang; Qi Shi; Xu Feng; Yan-Ping Yang; Yong-Jun Wang (World Journal of Traditional Chinese Medicine, 2015)
Yin-Yang theory plays critical role in traditional Chinese medicine (TCM) science. However, there are many competing interpretations of Yin-Yang theory in the context with the development in biology, and no consensus has been established. Here we first propose that osteoblast should be regarded as Yin, while osteoclast should be considered as Yang in bone remodeling compartment (BRC). Our conceptions are consistent with the following key findings: 1)osteoblast and osteoclast both derive from the embryonic ectoderm; 2)osteoblast and osteoclast work collaboratively in BRC to maintain bone homeostasis; 3)the activities of osteoblast and osteoclast are coupled to remain dynamic balance; 4)osteoblast and osteoclast exert their function in ceaseless successions. Moreover, we argue that Yin-Yang relationships exist between osteoblast and osteoclast: osteoblast secretes the receptor activator for nuclear factor-κB ligand (RANKL) and the monocyte/macrophage colony-stimulating factor (M-CSF) and osteoprotegerin (OPG) to positively or negatively regulate osteoclast differentiation and function. Meanwile, osteoclast and bone resorption in turn release cytokines, such as transforming growth factor-β (TGF-β), insulin-like growth factor-1(IGF-1) from bone matrix, to regulate osteoblast differentiation and function. Next, the unlimited division of Yin-Yang can be applied to divide sublevel of Yin-Yang inside osteoblast or osteoclast. Finally, Yin-Yang relationship of osteoblast and osteoclast is relative. Therefore, we come into the conclusion that the relationships between osteoblast and osteoclast as established in contemporary biology reflect the classic Yin-Yang in bone remodeling. The new Yin-Yang concepts of osteoblast and osteoclast may strengthen basic theory and clinical practice in TCM.